PRACTICAL EVALUATION of PHYTOSANITARYNPRODUCTS and ENVIRONMENTAL HEALTH RISKS in the ZIBAN REGION (Southeast Algeria) - Cheiakh , Mohamed Omar; Guimeur, Kamel; Mimeche, Fateh; Boumaraf , Belkacem (Journal of Economic Development, Environment and People, 2024)
This study assesses the knowledge and practices associated with pesticide use in a farming community. To assess the potential risks to human health and the environment posed by the phytosanitary practices of farmers in rural three localities in the Ziban region, a survey of 103 randomly selected greenhouse growers was performed between December 2019 and January 2020. The results revealed that 100% of greenhouse farmers did not undertake any protective measures (full clothing) from preparing the spray mixture to the end of the treatments. In addition, 67% of greenhouse growers dispose of sprayer-rinsed water on the ground next to the water source (irrigation borehole). Greenhouse growers dispose of 71.8% of pesticide packaging in the wild and burn 6.8% on the farm. The findings of this study reveal that the phytosanitary practices followed by greenhouse growers in the Ziban region are poor and could potentially threaten the health of applicators, consumers, and the environment.